Fungal species adhered to daily disposable contact lenses after wear - Lira, Madalena (2017)
Purpose: The objective of this study was to identify fungal species that are able to adhere to Daily Disposable Lenses (DDL), using both culture dependent methods and metagenomic analysis. Methods: In this study it was used a Daily Disposable Lens (DDL) Stenfilcon A. After 8 hour of wear, lenses were evaluated directly by isolation and identification by ITS sequencing and indirectly by a metagenomics analysis. In order to isolate and identify species presented in the DDL, the CL was incubated in YPS both medium for 12h at 30ºC and then 20μL of CL culture media was re-cultured in YPD agar plates at 30ºC for 48 hours. After incubation, the different colonies were isolated into new media and stored in 30% glycerol at -80ºC. The species identification was performed by ITS sequencing analysis. The microbiome analysis was performed using total DNA extracted before and after growth. The data used for the metagenomics analysis was obtained using RDP's Pipeline. Results: Only DNA from the culture after growth had the desirable concentration to be used metagenomic analyses. A total of 352206 Ascomycota and 104 Basidiomycota reads were obtained form the culture after growth. From these more than 99% were Saccharomycetes from the genera Candida (18331 reads). The fungal species that are frequently present in human epidermis such as Candida parapsilosis and Candida metapsilosis were found in high percentage. In addition, other species like Candida thea and Candida boleticola that may be found in aqueous solutions, such as water for domestic use, were also found in the metagenomic analysis. In the microbiological analysis of CL only Candida parapsilosis was the only species isolated in the cultivable analysis, overgrowing in comparison with the other species. Conclusion: This is the first study to identify Candida boleticola and Candida theae in DDL after wear. The species that can be found in water introduces a new variable in the compliance rule, since these species may be induced by the water used to wash the hands.